الغاز الطبيعي: طاقة عبور نحو التحول الطاقوي المستدام في الجزائر - رحمان, أمال; خوني, رابح (جامعة الوادي - University of Eloued, 2017)
يلعب الغاز الطبيعي دورا مهما وحيويا في قطاع الطاقة في الجزائر، واكتسى أهمية متزايدة منذ تسعينيات القرن العشرين. وتهدف هذه الدراسة إلى ابراز دور الغاز الطبيعي في تحقيق التحول الطاقوي في الجزائر من اقتصاد قائم على النفط إلى اقتصاد قائم على الطاقات المتجددة، حيث يمكن اعتباره كطاقة انتقالية تمهد الطريق للانتقال بسلاسة إلى الطاقة المتجددة. وقد تم الاعتماد على المنهج الوصفي التحليلي، وتم التوصل إلى مجموعة من النتائج أهمها أن الجزائر في دائرة التحول الطاقوي، ويمكن أن يساهم الغاز الطبيعي بدرجة كبيرة في تحقيق هذا التحول، إذا تم استغلاله بالشكل الأمثل. Natural gas plays an important and vital role in Algeria's energy sector and has assumed increasing importance since the 1990s. This study aims at highlighting the role of natural gas in achieving energy transition in Algeria from an oil-based economy to a renewable energy economy, so natural gas can be considered as a transitional energy that paves the way for a smooth transition to renewable energy. The analytical and descriptive method has been relied upon, and a set of conclusions has been reached, the most important of which is that Algeria is in the circle of energy transition, natural gas can contribute significantly to this transition, if it is optimally exploited
مقال
Keywords: تحول طاقوي، طاقات متجددة، غاز طبيعي، الجزائر; Natural gas: a transitional energy towards a sustainable energy transition in Algeria